Taxonomic significance of pollen morphology in Succisa and Succisella - Tsymbalyuk, Zoya M.; Mosyakin, Sergei L.; Nitsenko, Lyudmila M. (Biodiversity: Research and Conservation, 2020)
Pollen morphology of representatives of the genera Succisa and Succisella in the flora of Ukraine was studied using light and scanning electron microscopy. Pollen grains in both taxa were tricolpate, prolate, rarely oblate-spheroidal or spheroidal; large-sized. Their outline in polar view was subcircular, rarely trilobate, in equatorial view elliptical or rarely circular. Colpi short, of variable width, margins irregular with distinct, narrow margo, and blunt or acute ends. Exine sculpture was echinate-microechinate. The revealed characteristics of pollen grains are taxonomically significant at the generic and specific levels, and they can be used in pollen analysis. Palynomorphological data are consistent with the results of recent molecular phylogenetic studies. Data on pollen morphology also confirm taxonomic circumscription of Succiseae V. Mayer & Ehrend. Pollen grains in Succiseae are characterized by a tricolpate aperture type, which was probably ancestral in Dipsacaceae s. str.